Thermal Protective Properties of the Allomyrina dichotoma Beetle Forewing for Thermal Protection Systems. Issue 17 (8th November 2019) - Le, Vinh Tung; Ha, Ngoc San; Goo, Nam Seo
ABSTRACT: This paper studies the heat-shielding performance of a beetle forewing to explore how it has excellent thermal protective properties. With an experimental setup of a self-developed heating environment, the heat transfer characteristics of the beetle forewing were tested at 50°C under steady state conditions. Two types of the forewings are considered: cut wing and live wing. The heat transfer results show that the live forewing provides a good heat-shielding performance with the heat-shielding index stabilizing at around 22.1%, which is 60% higher than that of the cut wing. Based on scanning electron microscope images of the microstructure of the cross section of the beetle forewing, a simplified finite element analysis is performed to numerically calculate the heat transfer properties of the forewing. The numerical simulations reveal that the proposed structure of the forewing is good for the design of an effective thermal protection system. In addition, the uncertainty analysis is performed to evaluate the quality of experimental data. These results provide a foundational understanding of the heat transfer characteristics of beetle forewing, which will inspire a promising candidate for an actively cooled thermal protection systems.